Brief sexuality communication—a behavioural intervention to advance sexually transmitted infection/HIV prevention: a systematic review. (October 2014) - Cooper, B; Toskin, I; Kulier, R; Allen, T; Hawkes, S
Abstract : Background: Throughout the last decade substantial research has been undertaken to develop evidence‐based behaviour change interventions for sexual health promotion. Primary care could provide an opportunistic entry for brief sexual health communication. Objectives: We conducted a systematic review to explore opportunistic sexual and reproductive health services for sexual health communication delivered at primary health care level. Search strategy: We searched for studies on PubMed, ProQuest, CINAHL, Jstor, Scopus/Science Direct, Cochrane database of systematic reviews, EBSCO, CINAHL, PsychoInfo, and Web of Knowledge. Both published and unpublished articles were reviewed. Selection criteria: All randomised controlled trials and controlled clinical trials were included. Participants of all ages, from adolescence onwards were included. Brief (10–60 minutes) interventions including some aspect of communication on sexual health issues were included. Data collection and analysis: Data were extracted by two reviewers independently using a standardised form. Interventions differed from each other, hence meta‐analysis was not performed, and results are presented individually. Main results: A total of 247 articles were selected for full‐text evaluation, 31 of which were included. Sexually transmitted infections (STIs)/HIV were less often reported in the intervention group compared with the control group. Condom use was higher in most studies in the intervention group. Numbers of sexual partners and unprotected sexual intercourse were lower in the intervention groups. Conclusions: There is evidence that brief counselling interventions have some effect in the reduction and prevention of STIs/HIV. Some questions could not be answered, such as the effect over time and in different settings and population groups.